Mormon Trail, The Yesterday and Today - Hill, William (University Press of Colorado, 1996)
Back in print, this essential reference for readers interested in the Mormon Trail is part history, part resource book, part guide and photographic essay. It includes an historical introduction, a chronology, excerpts from trail diaries, along with maps, over 200 then-and-now photos, and descriptions of major museums and displays along the trail. By the author of previous volumes on the Oregon, California, and Santa Fe trails.